A guide to simple grammar - Yah Awg Nik; Khuzaiton Zakaria; Arifuddin Abdullah (Pearson, 2014)
A guide to simple grammar is meant for anyone who wants to learn English grammar the simple and effective way. We strongly believe trade, craft, or career learners are pursuing, it all starts with learning the basics. Hence, the key to speaking and writing good Enhlish lies with a good grasp of grammar